2010
DOI: 10.1080/09291011003687940
|View full text |Cite
|
Sign up to set email alerts
|

Co-sleeping and children's sleep in China

Abstract: Sleeping in the same bed as their parents is very common in young Chinese children, being present in up to 79% of pre-school children and 53% of schoolaged children. It is socially acceptable to Chinese parents as a natural part of the child-rearing process. Chinese family values and a cultural value system emphasizing family bonds and interpersonal interdependence seem to act as positive reinforcing factors for this practice of co-sleeping. Studies of Chinese children's sleep have focused primarily on some ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…3,9 Co-sleeping was reported as 46% in Chinese school children while it was only 5% in a study from Italy. 19,20 In the west even among infants and toddlers co-sleeping prevalence ranged from 5-36%. 21,22 Higher prevalence of co sleeping in the east could be due to socio-cultural factors where it is believed that children feel well loved and secure and secondly due to economic factors.…”
Section: Discussionmentioning
confidence: 99%
“…3,9 Co-sleeping was reported as 46% in Chinese school children while it was only 5% in a study from Italy. 19,20 In the west even among infants and toddlers co-sleeping prevalence ranged from 5-36%. 21,22 Higher prevalence of co sleeping in the east could be due to socio-cultural factors where it is believed that children feel well loved and secure and secondly due to economic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Stallones, with similar results in their study, showed that rural children had worse sleep quality and were more likely to injure themselves [ 31 ]. Huang et al [ 39 ] found that there was a larger incidence of co-sleeping among rural children than urban children because of the differences in socio-economic status and social values, and the sleep behaviors of children were easily influenced by co-sleeping, which tended to be associated with later bedtimes, bedtime resistance and daytime sleepiness, thereby, increasing the probability of risk of injury among rural children. Furthermore, compared to urban areas, there are more potential risk factors for injury in rural areas, which further contributes to the occurrence of injury [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, other factors, such as co-sleep, dangerous games or other high risk behaviors and children’s BMI, have not been taken into consideration in our study. Several previous studies showed that these factors could affect the sleep behaviors or play a positive/negative role in increasing risk of injury [ 39 , 40 ]. Finally, this was a cross-sectional study where we only summarized some tentative conclusions about the relationship between poor sleep behaviors and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Societal perspectives about infant sleeping location are culturally informed, and in western, high‐income countries, the prevalence of bed‐sharing varies between 13 and 50% (Ball & Volpe ). Bed‐sharing is commonly practiced in Confucian countries such as China, where it is part of a cultural values system that places importance on reinforcing family bonds (Huang et al ). Bed‐sharing was very common amongst participants in this study, which is consistent with previous research suggesting most (83%) Vietnamese families practiced bed‐sharing (Mindell et al ).…”
Section: Discussionmentioning
confidence: 99%